A Technical Overview on Beta-Attenuation Method for the Monitoring of Particulate Matter in Ambient Air - Kritika Shukla; Shankar G. Aggarwal (Aerosol and Air Quality Research)
Abstract Beta-attenuation technique is one of the widely used real-time technique for ambient particulate matter (PM) measurements since it allows continuous measurement while requiring minimal operator attention. Like any other technique, this method has several limitations that have been recorded in many studies. Beta-attenuation technique is dependent on the meteorological conditions as well as operational factors, which lead to over- or underestimation in the mass measurements in comparison to the reference method. However, the factors that affect its measurement and the variations in its performance under different conditions are not listed or reviewed in a comprehensive manner in a single document. Also, the systematic advancement of its development and implementation in ambient air measurements have not been documented in literature used by the air quality community. It is important for the user of this technique to have a detailed understanding of its principle and operation. Consequently, this article discusses the research, development, technology, and measurement of beta-attenuation method in depth. Although this review emphasizes primarily PM10 measurement results but some PM2.5 studies are also included. Our review reveals that federal equivalent method (FEM) designated beta gauge monitors in various studies performed better (with slope < 1.5 and intercept < 2 µg m−3) during high RH ambient conditions against reference or federal reference method (FRM). Studies related to PM10 showed that cut-off size, high mass loading and high ambient RH (> 80%) have impact on beta gauge measurements. Therefore, it is recommended to clean inlet once a week and use smart heater to control RH at or below 35%. PM2.5 studies also confirm the effect of relative humidity on beta gauge measurements.